2001
DOI: 10.1253/jcj.65.1029
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced ST-Segment Elevation Following Myocardial Infarction and Its Role in Wall Motion Abnormality, Myocardial Ischemia and Viability. Comparison of Response to Exercise, Dobutamine and Dipyridamole.

Abstract: tress-induced ST-segment elevation is a common finding in patients after myocardial infarction (MI), but its mechanism is still controversial. It has been interpreted as a sign of myocardial ischemia, 1,2 left ventricular wall motion abnormality (WMA) 3,4 or both, 5,6 and recent studies have suggested that ST-segment elevation during stress reflects myocardial viability. [7][8][9][10][11] Stress echocardiography has been proposed as a useful technique for the assessment of myocardial ischemia, left ventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, others have shown that in contrast to exercise and dobutamine, DIP did not induce ST segment elevation in similar patients [28].…”
Section: Discussionmentioning
confidence: 84%
“…However, others have shown that in contrast to exercise and dobutamine, DIP did not induce ST segment elevation in similar patients [28].…”
Section: Discussionmentioning
confidence: 84%